152k views
1 vote
PLEASE HELP ME NOW!!

PLEASE HELP ME NOW!!-example-1

2 Answers

4 votes

Hello!

The answer is:

The correct answer is the first option.


(x-4)^(2)=4+-2√(7)

Why?

To solve the problem, we must remember the following square root property:


√(ab)=√(a)√(b)

So,

We are given the expression:


(x-4)^(2)=28

Now, isolating we have:

First, applying square root to both sides of the equation in order to simplify the quadratic term, we have:


\sqrt{(x-4)^(2) }=√(28)\\(x-4)=√(4*7)\\\\x=4+-(√(4)*√(7))\\\\x=4+-2√(7)

Hence, the correct answer is the first option.


(x-4)^(2)=4+-2√(7)

Have a nice day!

User ChickenSoups
by
5.1k points
6 votes

Answer:


x=4+-2√(7)

Explanation:

To solve, we need to take square root of both sides first:


(x-4)^2=28\\√((x-4)^2) =+-√(28) \\x-4=+-√(28)

Now we use the property of radical shown below to simplify square root of 28:

Property:
√(x*y)=√(x) √(y)

Now, we have:


x-4=+-√(28)\\x-4=+-√(4*7)\\x-4=+-√(4)√(7)\\x-4=+-2√(7)

Now we take 4 to the other side and isolate x:


x-4=+-2√(7) \\x=4+-2√(7)

first answer choice is right.

User Sertorio Noronha
by
4.2k points